Computational Intelligence and Modern Heuristics - Ali, Al-Dahoud (IntechOpen, 2010)
The chapters of this book are collected mainly from the best selected papers that have been published in the 4th International conference on Information Technology ICIT 2009, that has been held in Al-Zaytoonah University, Jordan in the period 3-5/6/2009. The other chapters have been collected as related works to the topics of the book.